Fiscal calculus in a New Keynesian model with labor market frictions - Alessia Campolmi; Ester Faia; Roland Winkler (Magyar Nemzeti Bank, 2011)
During the Great Recession following the recent financial crisis large fiscal stimuli were implemented to counteract labor market sclerosis. We explore the effectiveness of various fiscal packages in a matching model featuring inefficient unemployment and a rich fiscal sector employing distortionary taxation and government debt. Results show that only stimuli directed toward the labor market, such as hiring subsidies, deliver large multipliers. Those policies can, indeed, abate the congestion externality, pervasive in the labor market. Various robustness checks confirm the results. The results obtained in the calibrated model are also confirmed through Bayesian estimation.
Keywords: E62; E63; E24; 330; fiscal calculus; taxation; matching frictions; bayesian estimation; Neukeynesianische Makroökonomik; Finanzpolitik; Geldpolitik; Öffentliche Ausgaben; Beschäftigung; Bayes-Statistik; Schätzung; USA